The Sunrise Model Approach to the Nutritional Status of Toddlers at the Kupang District Primary Health Center - Florentianus Tat; Aben B.Y.H Romana; Zainab Binti Mohd Shafie (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Nutritional problems in toddlers are still a major problem in East Nusa Tenggara Province. The 2018 Basic Health Research results show the percentage of malnourished babies aged 0-23 months in Indonesia was 3.8%, and malnutrition was 11.4%. East Nusa Tenggara is the province with the highest percentage of malnutrition among children aged 0-23 months in 2018. Nutritional problems have broad dimensions, such as socio-economic, cultural, educational, and environmental issues. The research objective is to determine the correlation between the sunrise model's factors and the toddler's nutritional status in the Kupang district. This study is a quantitative observational study with a cross-sectional design. The sampling technique in this study used accidental sampling. The research sample consisted of 169 people at 26 health centers. The results showed that there was a relationship between the use of health technology with the nutritional status of children under five (p=0.023), religious beliefs with family philosophy (p=0.024), family closeness (p=0.005), cultural and lifestyle factors (p=0.007), family economy (p=0.015), parental education (p=0.026), all variables have a significant relationship with the nutritional status of infants/toddlers (p=<0.05). It is concluded that there is a significant relationship between the factors in the sunrise model and the nutritional status of children under five in Kupang district. It is suggested that the sunrise model approach can be used to fix nutritional problems in children under five in Kupang Regency.